Thoracic Ectopia Cordis At Term With Severe Intrathoracic Effusion - Feldi Widianto; Febriani Febriani; Donel Suhaimi; Wiwin Suhandri; Munawar Adhar Lubis (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Ectopia cordis is an exceptionally rare congenital anomaly characterized by partial or complete displacement of the fetal heart outside the thoracic cavity. It represents a spectrum of defects encompassed within Cantrell’s pentalogy, a constellation of five major ventral midline abnormalities. With an estimated incidence of 5.5–7.9 per one million live births, ectopia cordis remains a profound diagnostic and management challenge in prenatal medicine. We describe a 24-year-old primigravida at 36 weeks of gestation who presented with uncontrolled hypertension and suspicion of fetal structural abnormalities. Ultrasonography confirmed a severely malformed fetal heart located outside the thoracic cavity, accompanied by marked intrathoracic fluid accumulation and persistent fetal bradycardia. Given the non-survivable nature of the anomaly and absence of feasible postnatal interventions, a vaginal termination was performed. A female neonate weighing 2900 g was delivered with Apgar scores of 4 and 5, demonstrating complete thoracic ectopia cordis. The prognosis of ectopia cordis remains extremely poor and depends largely on the type of ectopia, degree of cardiac exposure, and the presence of intracardiac or associated structural malformations. Despite advances in fetal imaging and neonatal cardiac surgery, survival is exceedingly rare. In pregnancies with lethal features, conservative prenatal management represents an ethically appropriate approach. This case underscores the importance of early diagnosis, comprehensive counseling, and multidisciplinary decision-making. Keywords: Ectopia Cordis, Congenital Anomaly, Cantrell’s Pentalogy, Fetal Diagnosis, Pregnancy Management.